Introduction to biostatistics: an overview of key concepts and applications - Adatorwovor, Reuben (Henry Stewart Talks, 2025)
Biostatistics, Terminologies in biostatistics, Data analysis, Survey methods in biostatistics, Experimental methods in biostatistics, Observational studies in biostatistics, Probability in statistics, Sampling techniques, Software used in biostatistics